2019
DOI: 10.1155/2019/9187609
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition and Associated Factors among Under-Five Children in Pastoral Communities of Afar Regional State, Northeast Ethiopia: A Community-Based Cross-Sectional Study

Abstract: Background. Malnutrition among children remains one of the most important causes of morbidity and mortality in the world. In Ethiopia, malnutrition is one of the most serious public health problem and the biggest in the world. This study aimed to assess the prevalence of malnutrition and associated factors among under-five children in pastoral communities of Afar Regional state, Northeast Ethiopia. Methods. A community-based cross-sectional study was conducted on 840 children aged 6–59 months from March 01–25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
109
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(185 citation statements)
references
References 42 publications
38
109
15
1
Order By: Relevance
“…Children who hadn't been breastfed exclusively for at least 6 months were 2.57 times more likely to get stunted. The study corporates similar studies performed in different areas among under ve children [40][41][42][43]. The probable reason is that inappropriate timing for introducing certain kinds of complementary food to a child can affect its nutritional status because its digestive and immune systems are not yet mature.…”
Section: Discussionsupporting
confidence: 74%
“…Children who hadn't been breastfed exclusively for at least 6 months were 2.57 times more likely to get stunted. The study corporates similar studies performed in different areas among under ve children [40][41][42][43]. The probable reason is that inappropriate timing for introducing certain kinds of complementary food to a child can affect its nutritional status because its digestive and immune systems are not yet mature.…”
Section: Discussionsupporting
confidence: 74%
“…The statistics tells us that even countries with advanced health systems are still struggling to cope with this epidemic. As the number of cases continues to rise outside China, moving to low-income countries, we should be deeply concerned about the impact it can pose to such population which for decades is characterized by high HIV prevalence [6], chronic non-communicable diseases [7], and malnourished individuals [8]. I think it is high time to report newly recorded incidences and provide clear recommendations while reflecting on China's experience.…”
Section: To the Editormentioning
confidence: 99%
“…Nine studies were from Amhara (21,38,61,72,75,76,80,82,85) and SNNPR regions (53,55,57,63,69,71,74,78,79). Studies in other regions included from Oromia (n=7) (22,51,54,62,67,73,83), Tigray (n=3) (60,65,66), Somalia(n=2) (52,70), Benishangul-Gumz(n=1) (84), and Afar(n=2) (64,77), and six studies were nation-based (56,58,68,81,86,87)(Table1). Three of the studies did not report sex of the study population, children (62,63,82), but all the other studies reported the sex of the children.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%